2016
DOI: 10.3389/fmicb.2016.01797
|View full text |Cite
|
Sign up to set email alerts
|

Different Virus-Derived siRNAs Profiles between Leaves and Fruits in Cucumber Green Mottle Mosaic Virus-Infected Lagenaria siceraria Plants

Abstract: RNA silencing is an evolutionarily conserved antiviral mechanism, through which virus-derived small interfering RNAs (vsiRNAs) playing roles in host antiviral defense are produced in virus-infected plant. Deep sequencing technology has revolutionized the study on the interaction between virus and plant host through the analysis of vsiRNAs profile. However, comparison of vsiRNA profiles in different tissues from a same host plant has been rarely reported. In this study, the profiles of vsiRNAs from leaves and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 46 publications
2
26
0
Order By: Relevance
“…Nevertheless, most studies of vsiRNA profiles in plants have used infected leaf tissue, and there is little evidence from other tissues. In our recent study of cucumber green mottle mosaic virus (genus Tobamovirus ) siRNAs from leaves and fruits, vsiRNAs in leaves were predominantly derived from the viral positive-strand RNA, whereas those in fruits were derived equally from both strands, suggesting that the biogenesis of vsiRNAs might differ in the different tissues ( Li J. et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, most studies of vsiRNA profiles in plants have used infected leaf tissue, and there is little evidence from other tissues. In our recent study of cucumber green mottle mosaic virus (genus Tobamovirus ) siRNAs from leaves and fruits, vsiRNAs in leaves were predominantly derived from the viral positive-strand RNA, whereas those in fruits were derived equally from both strands, suggesting that the biogenesis of vsiRNAs might differ in the different tissues ( Li J. et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several virus-plant interaction analyses have been performed at the transcriptional level to study both the physiological and metabolic processes variations of infected plants 21 23 . Virus-derived small interfering RNAs (vsiRNAs) profiles of CGMMV-infected cucumber 24 and different tissues from bottle gourd 25 have been investigated via high-throughput sequencing, and the results indicated that the characteristics of the vsiRNAs between different host plants or tissues were distinctly different. Eight novel and 23 known miRNAs have been identified that cucumber leaves produced in response to CGMMV infection, which is useful to help elucidate host-pathogen interactions as well as to screen for cucumber resistance genes 6 .…”
Section: Introductionmentioning
confidence: 99%
“…The read numbers of small RNAs were normalized to ‘reads per million’ (RPM) based on the total small RNA read numbers. The mapping of virus‐derived siRNAs to the combined virus genome sequence was carried out according to the method described previously (Li et al ., ).…”
Section: Methodsmentioning
confidence: 97%